PENGARUH BRAND EQUITY DAN BRAND TRUST TERHADAP LOYALITAS KONSUMEN MOBIL MEREK TOYOTA KIJANG INNOVA (Survey Konsumen Pada Dealer PT. Agung Automall Cabang Sutomo Pekanbaru) - Abas Bambang; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the influence of brand equity and brand trust on consumer loyalty Toyota Kijang innova car at PT. Agung Automall Pekanbaru. The sample in this study were taken 72 respondents and the technique used purposive sampling. The data in this study used survey method through questionnaires filled by consumers. Data obtained from the results of the questionnaire then processed tested with statistics through the program SPSS16. The results of analysis used multiple linear regression analysis, determination test (R2), individual significance test (t test) and simultaneous significance test (F test) so it can be seen that brand equity variable had a positive effect on consumer loyalty variable, brand trust variable influences variable loyalty Consumers, and a significant influence between brand equity and brand trust variables on consumer loyalty. The results shows R Square is the coefficient of determination and obtained R Square value of 0.747. That is, brand equity and brand trust affect consumer loyalty by 74.7%.Keywords : Brand Equity, Brand Trust, and Consumer Loyalty